Acute kidney injury in obstetrics: a five-year study in a tertiary centre - Papegowda, Sushma H.; Devi, Pratima K.; Singh, Ranjit L.; Muruganadam, Agalya; Tochhawng, Zikpuii L. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Pregnancy Related Acute Kidney Injury (PRAKI) is a major cause of maternal and foetal morbidity and mortality in developing countries. The incidence has declined due to improvements in reproductive health but it is still associated with significant perinatal mortality and maternal morbidity. It may be due to decrease in renal perfusion or ischemic tubular necrosis from a variety of conditions encountered during pregnancy. Our study aims at determining the predisposing factors and causes of AKI during pregnancy and its impact on maternal and foetal outcome. Methods: A retrospective cohort study over a period of 5 years was conducted on pregnant women with AKI as per inclusion and exclusion criteria. The detailed history, events, mode of delivery, cause leading to AKI, management, hospital stay, maternal and foetal outcome were studied in detail and evaluated. These patients were classified according to RIFLE criteria and were followed up for hospital stay and residual morbidities. Results: The incidence of PRAKI in the study was 0.07% (36 out of 50,735 deliveries) and among obstetric ICU patients, it was 6.8%. Most of the majority of the cases were unbooked (66.7%) and multipara (61.1%). Maternal morbidity was seen in 66.7% and mortality was 27.8%. Poor foetal outcome was seen in 44.4%. Conclusions: Haemorrhage is the most common cause of PRAKI, followed by toxaemia of pregnancy and sepsis. Early detection and meticulous management of haemorrhage, hypertension and sepsis reduce the incidence of PRAKI and associated maternal mortality.